The Difference Opinions Analysis on Conventional Bank Interest Law According to Ushul Fiqh - Chamim Tohari (IAIN Manado, 2019)
This research discussed conventional bank interest law according to the opinion of the Muslim scholars, which then will continue the discussion with the legal analysis based on the ushul fiqh theory to determine the strength of the conventional bank interest law. The most crucial problem examined in this research is how is prevailing bank interest law viewed from the perspective of usual fiqh? This research is library research. The approach used in this study is a conceptual approach considering the purpose to be achieved in this study is to produce one concept of Islamic legal thinking about bank interest law which is not bounded by existing views or opinions, but actually refers to the rules of Islamic law which is agreed upon by the majority of the muslim scholars. The results of this study are: The scholars have a different opinion on bank interest law. Those who forbid argued that bank interest has in common with usury, so it must be banned. As for those who justify bank interest explained that bank interest is not the same as usury, so its law is halal. As for those who consider it as a shubhat thing, because in their view the bank's interest besides having similarities with usury, also has a number of differences, so its law is shubhat. The bank interest law when viewed from the perspective of ushul fiqh, then both those that forbid, which justify, or those that consider syubhat, all of which do not originate from the qath'î, but zhannî propositions because they come from the results of ijtihad using the qiyâs method. Because of the absence of the qath 'argument, the author argues that the new direction to determine the halal-haram law of banking transactions with the interest system should be assessed from the large or small level of benefit (maslahah) and harm (mudharat) arising from the sale.